Answers

2015-02-04T06:56:15+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
25x² - 16y²
= (5x)
² - (4y)²
= (5x+4y)(5x-4y)
---------------------------------
2x² - 5xy - 3y²
2x² - 6xy + xy - 3y²
= 2x(x-3y) + y(x - 3y)
= (x-3y)(2x+y)
0
2015-02-04T12:18:52+05:30
1)
25x² - 16y²
⇒(5x)² - (4y)²
⇒ (5x + 4y)(5x - 4y)   [Using the formula a² - b² = (a +b)(a-b)

2) I think, the question should be 
2x²-5xy-3y²
2x² - 6xy + xy - 3y²
⇒ 2x(x - 3y) + y(x - 3y)
⇒ (x - 3y)( 2x + y) 

0